Clean development mechanism (CDM) vs. international permit trading - the impact on technological change - Cathrine Hagem (University of Oslo, Department of Economics, 2006)
The clean development mechanism (CDM) under the Kyoto Protocol may induce a technological change in developing countries. As an alternative to the CDM-regime, developing countries may accept a (generous) cap on their own emissions, let domestic producers invest in new efficient technologies, and sell the excess emission permits on the international permit market (cap&trade-regime). The purpose of this paper is to show how the gains from investment, and hence the incentive for investment in new technology may deviate between the two alternative regimes. We show that the difference in gains from investment depends on whether the producers face competitive or non-competitive output markets, whether the investment affects fixed or variable production costs and whether the producers can reduce emissions through other means than investment in new technology.
Keywords: L13; Q28; 330; Climate Policy; Technology Adoption; Emission Trading; Clean Development Mechanism; Technological Change; Duopol; Klimaschutz; Technischer Fortschritt; Innovationsdiffusion; Theorie; Emissionshandel; Clean Development Mechanism